Exposing Constitutional Violations: Vigilante Violence Against Northerners in Southern Nigeria - Abubakar Muhammad jibril (Fakultas Hukum Universitas Lampung, 2026)
Vigilante violence in Nigeria, particularly against Northerners in southern regions, exposes a gap between constitutional guarantees and lived reality. Although the Constitution of Nigeria protects the rights to life, equality, and security, weak enforcement has enabled recurring extrajudicial killings and ethnic profiling. This article examines whether such violence violates Section 33 (right to life), Section 42 (freedom from discrimination), and Section 14(2)(b) (state duty to ensure security and welfare). Using doctrinal and socio-legal analysis of constitutional provisions, case law, international instruments, and Amnesty International reports, the study finds persistent violations of life, patterns of indirect discrimination, and state failure to prevent and punish vigilante killings. These failures undermine constitutional legitimacy and national integration. The article recommends stronger accountability, disaggregated crime data, judicial enforcement of state obligations, and community-based initiatives to restore equal protection and the rule of law.